Jonson and the psychology of public theater : to coin the spirit, spend the soul - Sweeney, John Gordon, 1950- (Princeton legacy library, 1985)
This book is a study of Ben Jonson's relationship with his audience in the public theater, as the relationship changed in the course of his career from the comical satires to Bartholomew Fair. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.